COMPARATIVE ANALYSIS OF ANTONOMASIA IN ENGLISH AND UZBEK PRESS - Mustafoyeva Nodira Erkin qizi; Achilova Risolat Azamovna (Western European Studies, 2024)
This article discusses the broad definition and classification of antonomasia, various ways of its usage in speech, and comparisons with other forms of literary art. Additionally, the article presents several examples from both English and Uzbek press
Keywords: Antonomasia; linguistic device; rhetoric